1529. Suprapubic Catheter Placement Improves Antimicrobial Stewardship in a Veterans Affairs Long-term Care Facility. (26th November 2018) - Buehrle, Deanna J; Clancy, Cornelius J; Decker, Brooke K
Abstract: Background: It is unknown if suprapubic catheters (SCs) offer benefit over indwelling urethral catheters (IUCs) in incidence of asymptomatic bacteriuria and catheter-associated infection (CAUTI), or subsequent antibiotic exposure. Methods: We conducted a retrospective cohort study of unique patients with SCs placed at VA Pittsburgh Healthcare System from February 2015 to March 2018, who had a prior IUC (≥30 days for each). Demographic, laboratory, microbiologic, and antibiotic use data were compared over the same number of days between IUC and SC periods. IDSA Guidelines were used to define CAUTI and asymptomatic bacteriuria. Results: Eighteen patients with SC were included. SCs were in place for a median of 213 days (range: 49–1, 085). The indications for catheterization were urinary retention ( n = 12), neurogenic bladder ( n = 5), and decubitus healing ( n = 1). The most common underlying conditions were benign prostatic hyperplasia ( n = 9), multiple sclerosis ( n = 2), and Parkinson's disease ( n = 2). The median number of urine cultures collected per 100 IUC and 100 SC days were 2.28 (range: 0–4.08) and 0.35 (range: 0–5.85), respectively ( P = 0.02). Forty-four percent (8/18) and 39% (7/18) received at least one antibiotic course for asymptomatic bacteriuria during IUC and SC periods. A total of 170 days of antibiotic therapy were given for asymptomatic bacteriuria per 4, 881 IUC days vs. 107 days for asymptomatic bacteriuria per 4, 881 SC days ( P = 0.0001). The median rate of CAUTI was 0.25 per 100 IUC days vs. 0.08 per 100 SC days ( P = 0.15). The most common pathogens causing CAUTIs were Pseudomonas aeruginosa ( n = 5), Candida albicans ( n = 2), Klebsiella pneumoniae ( n = 1) and Enterococcus faecalis ( n = 1). A total of 163 days of antibiotic therapy were given for CAUTI per 4, 881 IUC days vs. 38 days of antibiotic therapy for CAUTI per 4, 881 SC days ( P < 0.0001). Conclusion: SCs were associated with significantly less overall antibiotic exposure than IUCs, both as treatment of CAUTIs and as inappropriate agents against asymptomatic bacteriuria. CAUTI rates were similar among patients with SCs and IUCs, although cultures were performed more often in those with IUCs. Reducing the treatment of asymptomatic bacteriuria remains a leading stewardship challenge. Disclosures: All authors: No reported disclosures.